THE LEGALITY OF BUYING AND SELLING WITHOUT KHIYAR RIGHTS UNDER ISLAMIC COMMERCIAL LAW - khairunnisak (Prodi Hukum Ekonomi Syariah, Fakultas Syariah dan Hukum, UIN Ar-Raniry, 2022)
Buying and selling is an activity that often occurs such as in markets, supermarkets and other places to fulfil everyone's needs. One of the elements in buying and selling transactions is the right of khiyär. Khiyar is a permissibility in Islamic Shari'ah to find a good between two, namely to continue or to cancel the sale with the aim of avoiding disputes between the seller and the buyer in the future. However, not all buying and selling places impose khiyar rights for buyers, therefore this research aims to find out how Islamic law reviews buying and selling without khiyar rights. Buying and selling without khiyar rights is still considered valid because khiyar is not a valid condition in buying and selling. Khiyar is an option or choice that can be an alternative to achieving benefits for both parties, namely the seller and the buyer so that no party feels disadvantaged in the future. Suggestions from the author that business actors are expected to apply business ethics in accordance with Islamic law and applicable legislation in Indonesia and for buyers to be more careful before buying goods so as not to be harmed.